Lessons Learned and Emerging Good Practices of ILO’s Syria Crisis Response in Jordan and Lebanon - International Labour Office (Beirut International Labour Organization (ILO), 2018)
"​The Syrian refugee crisis represents one of the largest, most protracted and complex humanitarian emergencies of modern times. Since 2011, the Syrian conflict has resulted in an estimated 5.6 million Syrians seeking refuge in neighboring countries. Lebanon and Jordan host the largest numbers of registered refugees per capita in the world. ILO adopted in 2016 the Guiding principles on the access of refugees and other forcibly displaced persons to the labour market. In order to operationalize these principles, within the framework of the Regional Refugee Response and Resilience Plan (3RP), the Jordan Response Plan, and the Lebanon Crisis Response Plan (LCRP), the ILO Regional Office for Arab states has adopted a development-focused and employment- driven strategy to support host communities and refugees in Jordan and Lebanon. Embedded in the principles of decent work, the ILO strategy builds on its core mandate to promote employment, social dialogue, social protection and international labour standards." (ILO Page)
​Pillar I - Support evidence-based policy development and strengthen institutional capacities for a well-coordinated, employment-rich national response -- Pilar II - Strengthen labour market governance for improved compliance with decent work principles, including the elimination of child labour -- Pillar III - Facilitate access to livelihood opportunities through labour-intensive work, skills development, and entrepreneurship development -- Conclusion Bibliography
Includes bibliographical references.
Keywords: Political refugees; POLITICAL REFUGEES; SYRIANS; LABOUR MARKET; CHILD LABOUR; ECONOMIC ASPECTS; ILO; DEVELOPMENT POLICY